The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/c9sm01803d
|View full text |Cite
|
Sign up to set email alerts
|

Phase behaviour and dynamical features of a two-dimensional binary mixture of active/passive spherical particles

Abstract: In this work we have characterized the phase behaviour and the dynamics of bidimensional mixtures of active and passive Brownian particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 27 publications
3
40
1
Order By: Relevance
“…There have been several studies examining bidisperse mixtures of passive and active particles which have shown that both motility induced phase separation and species separation can occur [61][62][63][64]. It has also been demonstrated that active particles can move passive particles and organize them into particular states even when there are only a small number of active particles present, which is known as active doping [65][66][67][68].…”
Section: Resultsmentioning
confidence: 99%
“…There have been several studies examining bidisperse mixtures of passive and active particles which have shown that both motility induced phase separation and species separation can occur [61][62][63][64]. It has also been demonstrated that active particles can move passive particles and organize them into particular states even when there are only a small number of active particles present, which is known as active doping [65][66][67][68].…”
Section: Resultsmentioning
confidence: 99%
“…Three main morphologies are observed: clusters of high density phase, bands that percolate the system, and bubbles of low density phase in a sea of high density phase. Both potentials seem to present all these phases, but in WCA they are considerably shifted towards higher densities, due to a greater overapping of particles, which results in a lower effective diameter 32 . The colours in figure 3 reflect the level of hexatic order of each particle, determined by ψ 6 .…”
Section: A How the Phase Diagram Depends On The Definition Of Pementioning
confidence: 99%
“…As in Ref. 32 we use the total density of the system instead of the packing fraction, in order not to depend on the particle's diameter. As an initial configuration, we prepare the system in a hexagonal lattice.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, it is possible to adapt well-established theoretical formalisms to the case of active matter to account for the most elemental properties of dissipative matter and the non-equilibrium transport and self-assembly of materials composed of active colloidal particles, see, e.g., Refs. [92,[104][105][106][107][108]. Undoubtedly, this is one of the most difficult problems, from conceptual point of view, and of greater scientific challenge that Colloidal Soft Matter Physics will face in the following decades.…”
Section: Active Colloidal Mattermentioning
confidence: 99%